Digital marketing based on social media marketing in marine tourism destinations - Rosida P. Adam (International Journal of Data and Network Science)
The aim of this research is to empirically test a new marketing model from a digital marketing perspective based on social media marketing, which is a crucial factor for consumers in the digital era when making decisions (especially tourists) to visit the Togean Islands marine tourism destination in Tojo Una-Una Regency. Social media marketing comprises three dimensions known as 4C: context, communication, collaboration, and connection. This type of research employs exploratory or confirmatory research methods. The data analysis method utilizes the PLS-SEM version 4 approach, and the research sample consists of 160 respondents, including both foreign tourists and Indonesian tourists. The research results indicate that the communication dimension has the highest loading factor value of 0.813, followed by collaboration with 0.770, connection with 0.745, and context with 0.703. Furthermore, the path coefficient value for the collaboration dimension is the highest compared to the other three dimensions, at 0.813. These findings imply that decision-makers can derive meaningful insights for redesigning new marketing models in the tourism sector amidst the digitalization era.